Stroke: Early Recognition and Emergency Management (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The early recognition and rapid emergency management of acute stroke are pivotal in minimizing permanent neurological damage and reducing global mortality rates. This paper proposes a comprehensive, integrated framework that bridges advanced medical imaging analysis with intelligent emergency coordination systems. By leveraging explainable artificial intelligence for initial lesion assessment and ontology-based cloud computing for resource routing, the system ensures both diagnostic safety and logistical efficiency. Ultimately, this unified approach aims to accelerate treatment timelines, overcoming the fragmented nature of traditional emergency healthcare networks.